1991
DOI: 10.1152/jappl.1991.70.5.2279
|View full text |Cite
|
Sign up to set email alerts
|

Renal neurohormonal and vascular responses to dynamic exercise in humans

Abstract: Effects of graded supine dynamic exercise (30, 60, and 80-90% of maximal physical capacity, i.e., work loads of 69, 132, and 188 W) on renal vascular resistance (RVR); renal sympathetic nerve activity [assessed by the renal venous overflow of norepinephrine (NE)]; renal overflows of dopamine (DA), immunoreactive neuropeptide Y (NPY-LI), and renin; as well as plasma concentrations of angiotensin-(1-8)-octapeptide (ANG II) were evaluated in eight healthy male volunteers. Exercise evoked stimulus-dependent and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 0 publications
4
49
0
Order By: Relevance
“…However, the exercise bout was performed at 50% of the individual maximal work load, leading to an approximately fivefold increase in oxygen uptake. Previous studies demonstrated that much lower intensity levels than those used in the present study are associated with a marked increase in sympathetic nerve activity (15,24). Therefore, we assume that our exercise protocol induced a significant increase in leg sympathetic nerve activity in controls.…”
Section: Limitationsmentioning
confidence: 50%
“…However, the exercise bout was performed at 50% of the individual maximal work load, leading to an approximately fivefold increase in oxygen uptake. Previous studies demonstrated that much lower intensity levels than those used in the present study are associated with a marked increase in sympathetic nerve activity (15,24). Therefore, we assume that our exercise protocol induced a significant increase in leg sympathetic nerve activity in controls.…”
Section: Limitationsmentioning
confidence: 50%
“…Wheels were removed from the cages of physically active animals just prior to surgery. This was done to reduce the effects of an acute bout of exercise on AVP and ANG II levels (51,53). Animals remained in the experiment room during the 2-day recovery period to acclimate to the experimental surroundings.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated previously that AngII, acting within the NTS, depresses the baroreceptor reflex via activation of endothelial nitric oxide synthase (eNOS; Paton et al 2001) and that endogenous eNOS activity within the NTS chronically depressed the sBRS in conscious rats (Waki et al 2003). Interestingly, circulating AngII increases during dynamic exercise (Tidgren et al 1991;Stebbins & Symons, 1995). Since circulating AngII may affect NTS neurones via eNOS activation (Paton et al 2001), we hypothesised that eNOS activity within NTS is one factor determining baroreceptor reflex function during dynamic exercise.…”
Section: Dynamic Exercise Attenuates Spontaneous Baroreceptor Reflex mentioning
confidence: 98%